(untitled) (Revista de Ciências Agroveterinárias, 2024)
The adaptability and stability of different genotypes are importants to help recommend cultivars. To achieve this, several methods have been proposed and the use of these methodologies simultaneously seems to allow the extraction of more consistent information than the use of each methodology separately. Therefore, the present work aims to study the adaptability and stability of sugarcane genotypes in terms of tons of sugarcane per hectare (TCH) in four environments in Mato Grosso do Sul and identify the superior genotypes through criteria multi-information. The TCH data were collected in the 2018/2019 harvest, in third-cut crops, from the experimentation phase of the Sugarcane Improvement Program of the Interuniversity Network for the Development of the Sugarcane Sector. The design used was a block design with three replications in which six early maturing clones (G1, G2, G3, G4, G5 and G6) and two commercial varieties (G7 - RB855156 and G8 - RB966928) were evaluated in four environments (1 - Ivinhema, 2- Rio Brilhante, 3- Nova Andradina Fazenda “N.O.” and 4- Nova Andradina Fazenda “E”. The joint analysis of variance was obtained from the data. The adaptability and stability of the genotypes was evaluated using multi-information, which included 10 parameters, being: the general average, average potential in different environmental conditions, plasticity, measure of the relative contribution to the interaction, Annicchiarico recommendation index, percentage adaptability, stability percentage, J pattern of genotype response, champion pattern and centroid recommendation index. Genotypes G3, G4, G6, G7 and G8 showed high stability and specific adaptation to high yield environments, such as environments 1 and 3. Genotype G6 surpasses commercial genotypes in yield. Genotypes G1, G2 and G5 present high stability, specific adaptation to low yield environments such as 2 and 4.